Serum Alpha-fetoprotein Levels and Response to Direct Antiviral Therapy in Patients with Chronic Hepatitis C: Real-world Results from 1716 Patients in Egypt - Badawi, Rehab; Alboraie, Mohamed; Abd-Elsalam, Sherief; Abourahma, Mohamed Z.; Ramadan, Haidi K.; Ahmed, Ossama A.; Fouad, Mohamed H.A.; Soliman, Shaimaa; Mohareb, Dina A.; Haydara, Tamer; Alnabawy, Sherein M.; El kassas, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background : Direct Antiretroviral Agents (DAAs), sofosbuvir-based therapies, have opened a new era in the treatment of chronic HCV infection. The aim of the study was to investigate the potential use of baseline and in serial serum, AFP levels as a predictor for response to DAAs in patients with Chronic Hepatitis C. Methods: This multicenter observational study was carried out on 1716 chronic hepatitis C virusinfected patients who received direct anti-viral drugs for 12 weeks. The primary end point was sustained virological response at 12 weeks after the end of treatment determined by quantitative PCR for HCV RNA. Serum AFP was quantitatively assessed at baseline then after 12week after stoppage of treatment (SVR12). Results: SVR12 rate was 97.8%. Elevated serum AFP was significantly higher in non -SVR group p value (<0.001). There was a significantly marked decrease in AFP after treatment in comparison to pretreatment values. The multivariate logistic regression analysis on the resulting significant variable from the univariate analysis revealed that only AFP was significantly related to the response to direct antiviral therapy in patients with chronic hepatitis C with p <0.001, OR 1.10 (95% CI 1.07:1.12). Other sociodemographic (e.g. Age, gender, BMI, ..) or laboratory factors (Hb, ANC, WBCs, …) did not show any significant association with the patients’ response to treatment. Conclusions: Serum AFP levels were a predictor for response in patients with chronic HCV with the administration of direct antiviral drugs.
Keywords: AFP